Argumentation and Persuasion Strategies in The Qur'an (The Story of Noah PBUH) | الحجاج في القرآن واستراتيجيات الإقناع: قصة نوح عليه السلام أنموذجا - Naous Benyahia (Al-Zahra : Journal for Islamic and Arabic Studies, 2020)
In general, this research aims primarily to highlight the most important persuasion strategies in the discourse of debate in the Qur'an through the conversations of Prophet Noah PBUH with his people. The story of Noah in delivering his preaching is mentioned several times in the Qur'an and its commentaries, especially in the Ruh al-Ma’any by Alusi and the Al-Hijjaj fi Al-Qur'an by Abdullah Shoula. Also, the other purpose is to show that the argumentation practice has existed since earlier time in the human history and argued Western research which states that Greece was the first to introduce arguments with the Sophists, Aristotle and others. Through the descriptive-analytical inductive approach, the article explores the subject of this research to explain clearly. This issue has been dealt with numbers of studies before but they did not focus on the practical side, and this is the main point differing this research to others.